Cold Water Immersion Improves the Recovery of Both Central and Peripheral Fatigue Following Simulated Soccer Match-Play - Bouchiba, Mustapha; Bragazzi, Nicola Luigi; Zarzissi, Slim; Turki, Mouna; Zghal, Firas; Grati, Mohamed Amine; Daab, Wael; Ayadi, Fatma; Rebai, Haithem; Ibn Hadj Amor, Hassen; Hureau, Thomas J.; Bouzid, Mohamed Amine (Frontiers in physiology, 2022)
The present study aimed to investigate the effect of cold water immersion (CWI) on the recovery of neuromuscular fatigue following simulated soccer match-play. In a randomized design, twelve soccer players completed a 90-min simulated soccer match followed by either CWI or thermoneutral water immersion (TWI, sham condition). Before and after match (immediately after CWI/TWI through 72 h recovery), neuromuscular and performance assessments were performed. Maximal voluntary contraction (MVC) and twitch responses, delivered through electrical femoral nerve stimulation, were used to assess peripheral fatigue (quadriceps resting twitch force, Q tw,pot ) and central fatigue (voluntary activation, VA). Performance was assessed via squat jump (SJ), countermovement jump (CMJ), and 20 m sprint tests. Biomarkers of muscle damages (creatine kinase, CK; Lactate dehydrogenase, LDH) were also collected. Smaller reductions in CWI than TWI were found in MVC (-9.9 ± 3% vs -23.7 ± 14.7%), VA (-3.7 ± 4.9% vs -15.4 ± 5.6%) and Q tw,pot (-15.7 ± 5.9% vs . -24.8 ± 9.5%) following post-match intervention ( p < 0.05). On the other hand, smaller reductions in CWI than TWI were found only in Q tw,pot (-0.2 ± 7.7% vs . -8.8 ± 9.6%) at 72 h post-match. Afterwards, these parameters remained lower compared to baseline up to 48–72 h in TWI while they all recovered within 24 h in CWI. The 20 m sprint performance was less impaired in CWI than TWI (+11.1 ± 3.2% vs . +18 ± 3.6%, p < 0.05) while SJ and CMJ were not affected by the recovery strategy. Plasma LDH, yet no CK, were less increased during recovery in CWI compared to TWI. This study showed that CWI reduced both central and peripheral components of fatigue, which in turn led to earlier full recovery of the neuromuscular function and performance indices. Therefore, CWI might be an interesting recovery strategy for soccer players.